2021
DOI: 10.1007/s10726-021-09758-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Comparison of Clustering Techniques for the Recognition of Communication Patterns

Abstract: The systematic processing of unstructured communication data as well as the milestone of pattern recognition in order to determine communication groups in negotiations bears many challenges in Machine Learning. In particular, the so-called curse of dimensionality makes the pattern recognition process demanding and requires further research in the negotiation environment. In this paper, various selected renowned clustering approaches are evaluated with regard to their pattern recognition potential based on high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Jun and Lee (2010) made use of objective selection criteria in which the algorithms are compared with each other by their silhouette score (Jun and Lee, 2010). Kaya and Schoop (2022) have discussed the research approach in which they mentioned how the clustering algorithm can be chosen objectively with the help of Silhouette index, Davies-Bouldin index etc.…”
Section: Choosing Clustering Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jun and Lee (2010) made use of objective selection criteria in which the algorithms are compared with each other by their silhouette score (Jun and Lee, 2010). Kaya and Schoop (2022) have discussed the research approach in which they mentioned how the clustering algorithm can be chosen objectively with the help of Silhouette index, Davies-Bouldin index etc.…”
Section: Choosing Clustering Methodsmentioning
confidence: 99%
“…Rousseeuw (1987) introduced silhouette index. Silhouette Score is complicated with respect to running time but at the same time it provides better information than elbow and Davies-Bouldin score (Kaya and Schoop, 2022). This index lies between -1 to 1.…”
Section: Choosing Clustering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "curse of dimensionality" [24,25] is a well-known one used to describe the issue. As a result, it has been discovered that numerous traditional anomaly detection methods [26][27][28] are inappropriate for high-dimensional data because they lose their effectiveness. In [29], the authors suggested a method for high-dimensional and categorical data anomaly detection.…”
Section: Introduction 1origin Of the Problemmentioning
confidence: 99%
“…One of the most active research areas is data clustering, among others [7][8][9]. Data clustering techniques can be used to perform similarity searches, pattern recognition, trend analysis, grouping, and classification, among other tasks [3,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%